Draft Five Year Plan 1978-83 Government of Gujarat - Planning Commission (Planning Commission, 1978)
It will be seen that the yield of rice has gone up from 685 Kg. per hectare in the Second Plan to 933 Kg. per hectare in the Fourth Plan. The increase in the yield of wheat is even more spectacular from 633 Kg. per hectare to 1557 Kg. per hectare. There have been substantial increases in the case of cotton and groundnut also.
Government of Gujarat, General Administration Department (Planning)